ANALYSIS OF MATERNAL MORTALITY IN A TERTIARY CARE HOSPITAL TO DETERMINE CAUSES AND PREVENTABLE FACTORS - Begum, Shamshad; Nisa, Aziz -un-; Begum, Iqbal (Journal of Ayub Medical College Abbottabad, 2003)
Background: All pregnant women are at risk of obstetrical complications and most of these occur during labour and delivery that lead to maternal death. In our setup maternal mortality is seriously under estimated. Safe motherhood as a priority for action can not be identified with out properly assessing maternal mortality. The objectives of this study were to determine causes and preventable factors responsible for maternal mortality. Methods: This study was conducted in Gynaecology ’˜C’ unit of Ayub Teaching Hospital, Abbottabad, from January 2000 to December 2001. Patients were admitted through emergency obstetrics care unit and Gynaecology out patient department. Patients’ demographic record including age, parity, education, socio-economic status along with antenatal care record, level of care and distance from hospital were noted. Causative factors leading to maternal death and contribution factors evaluated. All this information was collected from patients’ records. Results: Twenty-six maternal deaths were recorded during study period. The major causative factors were haemorrhage 9 (34.6%), eclampsia 8 (30%), sepsis 5 (19.2%), anaesthetic complications 3 (11.5%) and hepatic encephalopathy 1 (3.8%). Maternal mortality ratio was 12.7/1000 live births (26/2040). The age range was between 18-42 years. There were 16 (61.5%) patients in >30 years age group. Most of them (69%) were grand multiparas (Parity >5). Education, antenatal booking and socio-economic status were poor. The distance from hospital was between 10 and 100 KM. The level of care available at nearest health facility was estimated, 40% were attended by traditional birth attendants, 33% by lady health visitors, 10% by doctors and to 17% no level of care was available. Conclusion: Obstetrical haemorrhage and hypertensive disorders are still major causes of maternal deaths. Most maternal deaths are preventable. The provision of skilled care and timely management of complications can lower maternal mortality in our setup. Key Words: Maternal mortality, obstetrical complications, preventive measures.